2008
DOI: 10.1016/j.ygyno.2008.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate induces apoptosis in endometrial cancer cells

Abstract: Purpose-A recent landmark study demonstrated that Dichloroacetate (DCA) treatment promoted apoptosis in lung, breast, and glioblastoma cancer cell lines by shifting metabolism from aerobic glycolysis to glucose oxidation coupled with NFAT-Kv1.5 axis remodeling. The objective of this study was to determine whether DCA induces apoptosis in endometrial cancer cells and to assess apoptotic mechanism.Methods-A panel of endometrial cancer cell lines with varying degrees of differentiation was treated with DCA and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
170
7
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(201 citation statements)
references
References 39 publications
17
170
7
5
Order By: Relevance
“…DCA has been shown to attenuate 5-FU resistance in gastric cancer cells (14). In preclinical studies, different cancer cells showed different responses to DCA-induced apoptosis (32)(33)(34). We next investigated whether DCA would increase the effectiveness of 5-FU against colon cancer cells.…”
Section: Genetic or Pharmacological Inhibition Of Pdk4 Sensitizes Colmentioning
confidence: 99%
“…DCA has been shown to attenuate 5-FU resistance in gastric cancer cells (14). In preclinical studies, different cancer cells showed different responses to DCA-induced apoptosis (32)(33)(34). We next investigated whether DCA would increase the effectiveness of 5-FU against colon cancer cells.…”
Section: Genetic or Pharmacological Inhibition Of Pdk4 Sensitizes Colmentioning
confidence: 99%
“…In contrast, the efficacy of radiotherapy was sensitized by dichloroacetate with 150 mg/kg/d in vivo that gives much lower serum level of dichloroacetate. This finding is consistent with previous reports describing that this anti-metabolic compound has better in vivo efficacy than in vitro activity (37,46,47). The reasons for the limited antitumor effect of dichloroacetate with clinically relevant doses in vitro may lie in the complex cellular physiology and the immense excess of metabolites existing in cell culture media (46).…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we further analyzed the cell-cycle distribution after dichloroacetate treatment showing that dichloroacetate induced G 2 -M arrest and decreased the cell proportion in S-phase. These findings are consistent with some (35,36), but not all studies (12,37), indicating not all cancer types share the same mechanism of action after dichloroacetate treatment. As cancer cells are most sensitive to radiotherapy in the G 2 -M phase of the cell cycle whereas most resistance in the S-phase (38-40), our results suggest that dichloroacetate treatment can sensitize glioblastoma cells to radiotherapy by altering cell cycle-distribution.…”
Section: Discussionsupporting
confidence: 90%
“…Being an orphan drug, DCA is both nonpatentable and readily available, but it is not yet approved for use in cancer therapy (15). There is substantial preclinical evidence from both in vitro and in vivo models that DCA might be useful to treat cancer in humans, and a translation to earlyphase clinical trials would be of interest (16)(17)(18). Funding for such trials would be a challenge because DCA is a generic drug.…”
mentioning
confidence: 99%